Histopathological study of malignant lesion of Cervix in a tertiary care hospital of Nepal (Janaki Medical College Journal of Medical Science, 2022)
Background and objectives: Like in other developing countries, cancer of cervix is one of the leading malignancies in women in Nepal. In Nepal cervical pap-smear screening is not done my most of due to lack of awareness. The objective of this study is to find the prevalence of abnormal cervical epithelial lesions.Materials and methods: This was a retrospective study of 140 hysterectomy specimen reported from the Department of Pathology, Birat Medical College in Biratnagar. All tissue blocks of cervical tissues were retrieved, stained by Haematoxyline and Eosin (H & E) stain and re-examined. All the case was reviewed by consultant pathologist of Birat medical college.Results: In the present study out of 140 cases 08 ie.  5.71% have cervical epithelial neoplasia I.  1.42% cases is of CINII, 0.71 is of CINIII and 2.85% is squamous cell carcinoma.Conclusion: This study has demonstrated that 10.69% of the examined cases were abnormal. The squamous cell carcinoma is leading cancer in our study ie. 2.85%. In developing countries if patient is detected with abnormal pap smears then hysterectomy is indicated.